Product design competition under different degrees of demand ambiguity - Kauffeldt, Florian; Wiesenfarth, Boris Roland (Review of industrial organization, 2018)
Product differentiation decisions are frequently made under imperfect probabilistic information about consumer tastes (demand ambiguity). We investigate a Hotelling duopoly game of product-design-then-price choices that incorporates demand ambiguity. Our model allows for different levels of demand ambiguity. We find that the impact of ambiguity on product differentiation depends on firms’ ambiguity attitudes. Furthermore, our model generalizes the probabilistic model of Meagher and Zauner (J Econ Theory 117:201-216, 2004) and the non-probabilistic model of Krol (Int J Ind Org 30:593-604, 2012).